2009
DOI: 10.1007/s00044-009-9291-8
|View full text |Cite
|
Sign up to set email alerts
|

Microwave irradiation synthesis of novel ramose chitosan-based-5-fluorouracil and research on its in vitro release

Abstract: In order to construct a controlled release system of drugs and to reduce toxic side effects of 5-fluorouracil (5-FU), the novel ramose chitosan-based-5-fluorouracil (CSFU) was synthesized by a two-step method. First, ramose N,N-dicarboxyethyl chitosan (CECS) was efficiently synthesized from chitosan (CS) through microwave irradiation under mild alkaline media. Second, under the catalysis of EDC/NHS and using 5-Fu as a model drug, 1,3-bis(hydroxymethyl)-5-fluorouracil (HMFU) was successfully linked to the ramos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…As one of the most commonly prescribed anti-cancer agents, 5-FU, either alone or in combination with other anticancer agents, has been commonly applied for the treatments of various types of cancers 47 . A variety of chemically modified 5-FU derivatives have been synthesized to enhance their antitumor efficacy 48 , 49 , but their irregular oral absorption, low bioavailability and lack of specificity often result in poor clinical therapeutic outcomes 5 – 7 . In order to improve the oral bioavailability, a wide variety of polymers have been synthesized for direct or indirect attachment of 5-FU and its derivatives 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most commonly prescribed anti-cancer agents, 5-FU, either alone or in combination with other anticancer agents, has been commonly applied for the treatments of various types of cancers 47 . A variety of chemically modified 5-FU derivatives have been synthesized to enhance their antitumor efficacy 48 , 49 , but their irregular oral absorption, low bioavailability and lack of specificity often result in poor clinical therapeutic outcomes 5 – 7 . In order to improve the oral bioavailability, a wide variety of polymers have been synthesized for direct or indirect attachment of 5-FU and its derivatives 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has significant merits such as reducing side reactions and being solvent-free. 17,18 Therefore, it is our aim to combine ultrasound and microwave irradiation together in order to examine the inter-particle interactions that will bring striking changes in morphology transformation, composition and properties. In this study, SrWO 4 :Ln 3+ (Eu 3+ , Tb 3+ , Sm 3+ and Dy 3+ ) phosphors were successfully prepared in the presence of co-irradiation by both supersonic and microwave treatments under very low temperature (70 °C) in only 45 min.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, using the EDC / NHS as catalysts, CS-FU was synthesized successfully at room temperature. 9 It was found that reaction time was the most important influence factor in this reaction. The influence of reaction time on the drug loading and gel formation were shown in Fig.…”
Section: Synthesis Of Cs-fumentioning
confidence: 97%